Innovative Practices in Contemporary Chinese Industrial Ceramic Design: Portability, Biodesign, and Materials - Xie, Jixian (Культура и искусство, 2025)
The subject of the research is innovative practices in contemporary Chinese industrial ceramic design, considered through the prism of portability, biodesign and material innovation. The object of the research is the process of transformation of traditional Chinese ceramic culture. The author examines in detail the evolution of portable tea sets as a representative objects demonstrating the mechanisms of adaptation of traditional ceramic utensils to the conditions of the mobile lifestyle of the 21st century. Particular attention is paid to the analysis of material innovations, including experiments with combined materials and the introduction of digital design tools that expand the constructive and expressive possibilities of ceramic products. The research methodology is based on the historical and cultural analysis of the evolution of ceramic technologies from the 8th century to the present day, an interdisciplinary approach to the study of material culture and a comparative analysis of specific design solutions in the field of industrial design. The main conclusions of the study are that portable tea sets provide adaptation of traditional tea utensils to the requirements of a mobile lifestyle while maintaining the ritual and aesthetic component of the tea ceremony, biodesign strategies implement the actualization of traditional cultural archetypes through the use of natural forms, textures and symbolic images in a modern visual environment. The novelty of the study lies in the comprehensive analysis of modern innovative practices in Chinese ceramic design through the identification of three interrelated areas of development - portability, biodesign and material experiments, which have not previously been considered in the scientific literature as a holistic system for transforming traditional ceramic culture. For the first time, mechanisms for integrating traditional cultural meanings with modern design approaches in the field of portable ceramic products have been established, patterns of technological transfer from historical ceramic practices of the 8th century to current design solutions using parametric solid modeling and VR technologies have been revealed. The obtained results allow us to formulate conceptual foundations for the further development of the theory of industrial design of ceramic products and the practical application of the identified principles in design activities, which opens up prospects for the creation of functional ceramics adapted to the modern lifestyle.